Pengaruh Kepemimpinan Kepala Sekolah, Profesionalisme Guru dan Motivasi Kerja terhadap Mutu Sekolah - Salik, Umdatus; Juliejantiningsih, Yovitha; Sudana, I Made (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
Abstract School quality is the school's ability to provide quality education that meets needs and expectations in accordance with current developments and technology. The quality of several state junior high schools in sub-rayon 3 Jepara Regency is less than optimal, namely that students' achievements in school exams have not met expectations, they have not been ranked in the top five, and their quality report cards are still below ideal figures. Increasing the leadership role of school principals, teacher professionalism and teacher work motivation can have a positive influence on the quality of schools in SMP Negeri sub-rayon 3 Jepara Regency. The objectives of this study are to determine: (1) the influence of school principal leadership on school quality; (2) the influence of teacher professionalism on school quality; (3) the influence of teacher work motivation on school quality; (4) the combined influence of school principal leadership, teacher professionalism, and teacher work motivation on school quality in public junior high schools in Sub District 3, Jepara Regency. This research employs a quantitative approach with a non-experimental ex post facto design. The population consists of junior high school teachers in Sub District 3, Jepara Regency, with a sample of 302 teachers selected using proportional random sampling techniques. Data collection methods include questionnaires or surveys. Data analysis involves descriptive analysis, testing requirements, and hypothesis testing using simple linear regression and multiple linear regression analyses with SPSS software. Based on the research findings, it was found that: (1) school principal leadership has a significant influence on school quality by 47.2% and a strong relationship with a correlation value of 0.687; (2) teacher professionalism has a significant influence on school quality by 45.5% and a strong relationship with a correlation value of 0.674; (3) teacher motivation has a significant influence on school quality by 8.5% and a moderate relationship with a correlation value of 0.291; (4) school principal leadership and teacher motivation jointly have a strong simultaneous influence on school quality by 52.4% and a strong relationship with an average correlation value of 0.55. It is recommended that school principals enhance leadership competencies, promote teacher professionalism, and motivate teacher performance to achieve superior school quality. The implications of this research are programs to increase the competency of school principals, professional development according to teacher needs and measuring teacher work motivation with appropriate instruments. Keywords: school principal leadership, teacher professionalism, work motivation, school quality